Ultrafast Terahertz Complex Conductivity Dynamics of Layered MoS2 Crystal Probed by Time-Resolved Terahertz Spectroscopy - Yang, Yong; He, Chuan; Huang, Yuanyuan; Zhu, Lipeng; Zhou, Yixuan; Xu, Xinlong (Frontiers in Physics, 2021)
Ultrafast carrier dynamics, including the carrier photoexcitation and relaxation processes, play an essential role in improving the performance of molybdenum disulfide (MoS2)-based optoelectronic devices. Herein, we investigate the photo-generated carrier dynamics in layered MoS2 crystal using a time-resolved terahertz (THz) spectroscopy. We have analyzed the ultrafast changes of the THz complex photoconductivity deduced from the peak and zero-crossing of THz waveforms. The decay time of the real THz photoconductivity in layered MoS2 crystal is independent with the pump power, while the imaginary part increases with the pump power. We attribute the real part to the carrier recombination process via phonon-assistance and the imaginary part to the defect-assisted exciton recombination. The peak values of the complex photoconductivity show a trend of saturation with increasing the pump power because of the many-body effect at high carrier concentration. This work deepens the understanding of the basic ultrafast physical process in MoS2 crystals, which is enlightening for the design of novel optoelectronic devices.